Revisit of combined parallel-beam/cone-beam or fan-beam/cone-beam imaging - Zeng, Gengsheng L. (American Association of Physicists in Medicine, 2013)
Purpose: This aim of this paper is to revisit the parallel-beam/cone-beam or fan-beam/cone-beam imaging configuration, and to investigate whether this configuration has any advantages. Methods: Twenty years ago, it was suggested to simultaneously use a parallel-beam (or a fan-beam) collimator and a cone-beam collimator to acquire single photon emission computed tomography data. The motivation was that the parallel-beam (or the fan-beam) collimator can provide sufficient sampling, while the cone-beam collimator is able to provide higher photon counts. Even with higher total counts, this hybrid system does not give significant improvement (if any) in terms of image noise and artifacts reduction. If a conventional iterative maximum-likelihood expectation-maximization algorithm is used to reconstruct the image, the resultant reconstruction may be worse than the parallel-beam-only (or fan-beam-only) system. This paper uses the singular value decomposition (SVD) analysis to explain this phenomenon. Results: The SVD results indicate that the parallel-beam-only and the fan-beam-only system outperform the combined systems. Conclusions: The optimal imaging system does not necessary to be the one that generates the projections with highest signal-to-noise ratio and best resolution.